Chitosan-Functionalized Poly(β-Amino Ester) Hybrid System for Gene Delivery in Vaginal Mucosal Epithelial Cells - Xueqin Gao; Dirong Dong; Chong Zhang; Yuxing Deng; Jiahui Ding; Shiqi Niu; Songwei Tan; Lili Sun (MDPI AG, 2024)
Gene therapy displays great promise in the treatment of cervical cancer. The occurrence of cervical cancer is highly related to persistent human papilloma virus (HPV) infection. The HPV oncogene can be cleaved via gene editing technology to eliminate carcinogenic elements. However, the successful application of the gene therapy method depends on effective gene delivery into the vagina. To improve mucosal penetration and adhesion ability, quaternized chitosan was introduced into the poly(β-amino ester) (PBAE) gene-delivery system in the form of quaternized chitosan-g-PBAE (QCP). At a mass ratio of PBAE:QCP of 2:1, the polymers exhibited the highest green fluorescent protein (GFP) transfection efficiency in HEK293T and ME180 cells, which was 1.1 and 5.4 times higher than that of PEI 25 kD. At this mass ratio, PBAE-QCP effectively compressed the GFP into spherical polyplex nanoparticles (PQ-GFP NPs) with a diameter of 255.5 nm. In vivo results indicated that owing to the mucopenetration and adhesion capability of quaternized CS, the GFP transfection efficiency of the PBAE-QCP hybrid system was considerably higher than those of PBAE and PEI 25 kD in the vaginal epithelial cells of Sprague-Dawley rats. Furthermore, the new system demonstrated low toxicity and good safety, laying an effective foundation for its further application in gene therapy.